Running Dictations Game to Students Writing Skills - Seriani Hutasuhut; Hotdalila Daulay (UIN Syekh Ali Hasan Ahmad Addary Padangsidimpuan, 2022)
This research is intended to investigate the effect of Running Dictations Game to Students Writing Skills at the Second Grade of MTs Mardhotillah Boarding Tapanuli Selatan. This research was designed with quantitative research with experimental method. The sample were VIII B as experimental class that consisted of 11 students and VIII C as control class that consisted of 10 students. The data were collected through pre-test and post-test in oral test type dictation directly that given by teacher and analyzed by using t-test formula. The finding showed that the mean score of experimental class was higher than the mean score of control class. After doing T-test, the researcher found that tcount ttable (6.49 2.093). Therefore, alternative hypothesis (Ha) of this research was accepted null hypothesis (H0) was rejected. It can be concluded that there was significant effect of using Running Dictations Game to Students Writing Skills at the Second Grade of MTs Mardhotillah Boarding Tapanuli Selatan.